Oral azithromycin versus doxycycline in meibomian gland dysfunction: A hospital-based study at Nepal eye hospital - Dhakal, Sabita; Sabina Shrestha; Pooja Karki; Sujata Dhakal (Asian Journal of Medical Sciences, 2025)
Background: Meibomian gland dysfunction (MGD) involves posterior blepharitis, which includes a disruption of the tear and meibum lipids and thereby produces an evaporative dry eye. The most common cause is obstruction of the meibomian glands, which causes inflammatory changes and increases bacterial colonization along the lid margins. Conservative management consists of warm compresses, mechanical eyelid massage, and artificial tears; when severe, an oral antibiotic with anti-inflammatory properties can be suggested. Aims and Objectives: The aims and objectives of the study are to compare the effects (symptom and sign scores) and safety (side effects) of oral azithromycin compared with oral doxycycline in patients with posterior blepharitis. Materials and Methods: This is a prospective, comparative, and randomized hospital-based study conducted at Nepal Eye Hospital from June 2016 to December 2017. This study recruited patients having severe MGD. Convenience sampling technique was used for the selection of patients. Result: A total of 60 patients with 30 in each group ranging in age from 21 to 74 years were included. Both groups experienced a significant improvement in symptoms and indicators (P=0.001). Ocular surface staining (P=0.04) and bulbar conjunctival redness (P=0.02) were significantly better in the azithromycin group, but symptom improvement was not different between the groups. When the doxycline group experienced more side effects in the 3rd week, there was no discernible difference in the mild gastrointestinal side effects between the groups. Conclusion: This study showed that oral doxycycline and azithromycin are beneficial to patients with MGD patients. Due to superior clinical improvement, shorter treatment duration, low cost, and side effects, 5-day oral azithromycin is recommended in comparison to 1-month oral doxycycline.